Nonliner damping of electron beam-driven Langmuir waves due to Langmuir-kinetic Alfvén-whistler coupling in the solar corona - Sirenko, O.K.; Voitenko, Yu.M.; Goossens, M.; Chian, A.C.-L. (Вопросы атомной науки и техники, 2007)
We present a coherent nonlinear theory of three-wave coupling involving Langmuir, kinetic Alfvén and whistler waves. The initial stage of the energy exchange among these modes and the following nonlinear temporal dynamics are studied. The role of pump depletion, dissipation and frequency mismatch in the nonlinear wave dynamics is analyzed. Depending on the relative damping rates of the waves, the initial Langmuir waves can be nonlinearly transformed either into whistlers, or into KAWs. The theory is applied to the Langmuir waves excited by electron beams in a diluted solar corona where the local electron-cyclotron frequency is higher than the local electron plasma frequency. Представлена когерентна нелінійну теорія трихвильової взаємодії, що включає ленгмюрівську, кінетичну альфвенівську хвилі та вістлер. Вивчена початкова стадія енергетичного обміну між даними хвилями та його наступна часова динаміка. Проаналізовано вплив зміни амплітуди хвилі накачки, вплив диссипації та частотного зсуву на нелінійну хвильову динаміку. В залежності від відносного затухання хвиль, початкові ленгмюрівські хвилі можуть бути нелінійно трансформовані або в вістлери, або в кінетичні альфвенівські хвилі. Результати теорії застосовані для ленгмюрівських хвиль, що збуджуються електронним пучком в розрідженій корональній плазмі, де локальна електронно-циклотронна частота більша за локальну електронну плазмову частоту. Представлена когерентная нелинейная теория трехволнового взаимодействия ленгмюровской, кинетической альфвеновской волн и вистлера. Изучена начальная стадия энергообмена между данными волнами и его последующая временная динамика. Проанализировано влияние изменения амплитуды волны накачки, влияние диссипации и частотного сдвига на нелинейную волновую динамику. В зависимости от относительного затухания волн начальные легмюровские волны могут быть нелинейно трансформированы или в вистлеры, или в кинетические альфвеновские волны. Результаты теории применены для ленгмюровской волны, которая возбуждается электронным пучком в разреженной корональной плазме, где локальная электронно-циклотронная частота больше, чем локальная электронная плазменная частота.